Community Construction Toward Former Narcotics Abusers in Wates Urban Village, Mojokerto City - Valensyah Julian Nayomi (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This study discusses the social construction of society toward former narcotics abusers in Wates Urban Village, Mojokerto City. The problem of narcotics abuse not only affects legal and health aspects but also gives rise to social stigma that hinders the rehabilitation process and social reintegration of former abusers. This research aims to understand how society’s social construction toward former narcotics abusers is formed and to analyze the factors influencing it. The study employed a qualitative method with a case study approach. Data were collected through interviews, observations, and documentation involving the residents of Wates Urban Village, former narcotics abusers, community leaders, and officers of the Mojokerto City National Narcotics Agency (BNN). Data analysis was conducted through data reduction, data presentation, and conclusion drawing using the social construction theory of Peter L. Berger and Thomas Luckmann. The results of the study indicate that society still constructs negative stigma toward former narcotics abusers through the processes of externalization, objectification, and internalization. Labels such as “criminal” and “social threat” create difficulties in obtaining employment, social acceptance, and environmental support. However, the Community-Based Intervention (CBI) program has begun to encourage changes in public perception, making society more supportive of the rehabilitation process. This study concludes that community social support plays an important role in the successful social reintegration of former narcotics abusers.